Pengaruh Beban Kerja dan Fleksibilitas Jadwal Kerja terhadap Work-Life Balance Karyawan Shift di Hotel Ibis Semarang Simpang Lima - Siska Berliana Giawa; Renny Aprrilliyani (Mahesa Research Center, 2025)
This article aims to analyze the influence of workload and work schedule flexibility on the work-life balance of shift employees at Hotel Ibis Semarang Simpang Lima. The problem focuses on how high workload and limited schedule flexibility affect employees’ ability to balance work and personal life. To approach this issue, the study applies the Job Demands-Resources (JD-R) and Work-Family Balance Theory as theoretical frameworks. Data were collected through a closed-ended questionnaire distributed to 48 shift employees and analyzed quantitatively using multiple linear regression with SPSS version 26. The results show that workload and work schedule flexibility simultaneously have a significant effect on work-life balance, with a coefficient of determination (R²) of 0.658. Partially, both variables have a positive and significant effect, with schedule flexibility being the most dominant factor. This study concludes that managing workload proportionally and implementing flexible scheduling policies are crucial in achieving employees’ work-life balance.